Histamine Detection in Mackerel (Scomberomorus Sp.) and its Products Derivatized with 9-Flourenilmethylchloroformate - Muhammad Abdurrahman, Munir; Lee, Yook Heng; Edison Eukun, Sage; Muhammad Mukram, Mohamed Mackeen; Khairiah, Haji Badri (National Centre of Excellence in Analytical Chemistry, 2021)
Histamine is commonly present in food containing proteins, like in mackerel. Consuming fish is imperative for the improvement of human muscles. Nevertheless, some studies reported ingesting fish containing histamine more than 50 mg·kg-1 can cause toxicity. This study analyzed and determined the composition of histamine in mackerel and its products commonly consumed in Malaysia, especially on the East Coast of Malaysia. These included processed mackerel such as canned products, satay (skewed fish) and keropok lekor (fish cake/ cracker). Histamine analysis was performed using High Performance Liquid Chromatography (HPLC) equipped with a fluorescence detector. A derivatizing reaction was applied to increase the sensitivity of HPLC to histamine using 9-flourenilmethylchloroformate (FMOC-Cl). The chromatographic separation was achieved in 15 min. Method validation was in accordance to Commission Decision 657/2002/CE. The linear range was at 0.16 – 5.00 µg·mL-1 (histamine) with the LOD at 0.10 µg·mL-1 and LOQ at 0.30 µg·mL-1 . Method applicability was checked on seven real samples involving raw, cooked, and dry products, yielding acceptable recovery.